TEKNOLOGI INFORMASI E-COMPLAINT PADA PERGURUAN TINGGI - Fitria -; Muhammad Fauzan Azima; Sulyono - (IIB Darmajaya, 2018)
About the quality of campus management and already have an international standard internal quality assurance system. Handling complaints is important, because in a good handling process it will affect the reputation of the agency / company. The purpose of this study is to design and build an information technology that can accommodate complaints, criticisms and suggestions on the operational part of the campus and lecturers who are on the Darmajaya IBI in the form of E-Complaint. The stages of system development used are using the SDLC waterfall model, often called a linear sequential model. This e-complaint application makes it easy for IBI Darmajaya students to provide complaints (complaints) and criticisms and suggestions to the operational part of the campus and lecturers. This application uses a bootstrap framework that is able to manage the appearance of the application to be responsive. By being responsive, the application can adjust the shape on various device sizes. This application is useful to help the Quality Assurance Center (QAC) which functions as a quality assurance agency for a campus.Keywords: Application, E-complaint, Mobile Website, Responsive, Information Technology